A Synthetic Pan-Aurora Kinase Inhibitor, 5-Methoxy-2-(2-methoxynaphthalen-1-yl)-4H-chromen-4-one, Triggers Reactive Oxygen Species-Mediated Apoptosis in HCT116 Colon Cancer Cells - Jeong Yeon Lee; Sung Shin Ahn; You Jeong Jeong; Jihye Choi; Seunghyun Ahn; Dongsoo Koh; Young Han Lee; Yoongho Lim; Soon Young Shin (Journal of Chemistry)
Aurora kinases are Ser/Thr kinases that function as mitotic regulators. 5-Methoxy-2-(2-methoxynaphthalen-1-yl)-4H-chromen-4-one (DK1913) is a synthetic pan-Aurora kinase inhibitor. However, the mode of action of DK1913 concerning the induction of apoptosis is unclear. Here, we report that DK1913 triggered apoptosis, as revealed by flow cytometry and Annexin V staining. DK1913 enhanced the intracellular levels of reactive oxygen species (ROS) and stimulated the endoplasmic reticulum (ER) and genotoxic stress responses. We also found that DK1913 induced the loss of mitochondrial membrane potential, leading to the activation of caspase-9, caspase-7, and caspase-3. In addition, the antioxidant, butylated hydroxyanisole (BHA), abrogated DK1913-induced loss of mitochondrial membrane potential and activation of the caspase cascade. These findings demonstrate that pan-Aurora kinase inhibitor DK1913 triggers apoptosis through ROS-mediated ER and genotoxic stress responses.